Instant terpolymer emulsion type fracturing fluid thickening agent and preparation method thereof
The instant terpolymer emulsion-type fracturing liquid thickening agent prepared by copolymerizing new cationic monomers and other monomers solves the problems of long dissolution time and single function of the existing thickening agent, and achieves rapid dissolution and multifunctional performance, and is suitable for offshore oil and gas and shale oil and gas fracturing operations.
Patent Information
- Application Number
- CN202510213247.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-26
AI Technical Summary
The existing fracturing liquid thickening agent has a long dissolution time, a single function and cannot meet the needs of different geological conditions, making it difficult to effectively apply in offshore oil and gas and shale oil and gas fracturing operations.
By synthesizing a new cationic monomer and copolymerizing with nonionic monomers and anionic monomers, an instant terpolymer emulsion fracturing liquid thickening agent is prepared, which has excellent drag reduction and thickening properties, and is suitable for different geological conditions.
It achieves rapid dissolution of thickeners, good viscoelasticity, salt resistance and temperature resistance and glue breaking properties, meets the needs of offshore oil and gas and shale oil and gas fracturing operations, and improves construction efficiency and operating results.
Smart Images

Figure CN119899313A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a fracturing fluid thickener system and relates to a synthetic polymer fracturing fluid thickener and a preparation method thereof. Background Art
[0002] Fracturing technology is one of the main measures to increase production in oil and gas fields. Its purpose is to press cracks into the reservoir to increase production. The performance of fracturing fluid is directly related to construction efficiency. With the continuous development of oil exploration technology, the development of oil and gas fields continues to extend vertically, and the geological conditions of underground reservoirs are diverse, including porosity, permeability, rock type and other factors. Some formations may need to inject slippery water during fracturing operations to reduce friction resistance, while some formations may need to use sand-carrying fluids during fracturing operations to increase crack stability. Existing fracturing fluids are usually composed of additives such as thickeners, cross-linking agents, anti-swelling agents, and bactericides. Among them, thickeners are the main additives in the fracturing fluid system. Thickeners can be divided into solid powder type and emulsion type. Solid powder types have problems such as the need to prepare liquid in advance for construction, low construction efficiency, single function, and inability to meet the needs of different reservoir transformation environments at the same time. Chinese patent CN115703724A discloses a sulfonic acid compound and a quick-dissolving polyacrylamide for oil recovery with heat resistance and salt resistance and its preparation method and application. The solubility of the polymer is improved by introducing a sulfonic acid group, and the rigidity of the molecular chain structure is increased by introducing a benzene ring group. However, the actual dissolution time of polyacrylamide is still not ideal. The dissolution time exceeds 40min at 20,000 mineralization degrees and 80°C, which is difficult to meet the needs of field applications. Chinese patent CN109134752A discloses a quick-dissolving polyacrylamide for offshore oil recovery and its synthesis method. The quick-dissolving polyacrylamide synthesized with acrylamide and 2-acrylamide-2-methylpropane sulfonic acid as monomers has an unsatisfactory quick-dissolving effect. It dissolves slowly at 32,000 mineralization degrees and 85°C, which cannot meet the needs of field applications. Therefore, it is urgent to develop a fracturing fluid thickener with good quick-dissolving effect, which can flexibly adjust the concentration under different geological conditions to meet the needs of offshore oil and gas fracturing operations and shale oil and gas fracturing operations. Summary of the invention
[0003] In order to improve the instant dissolution effect of the fracturing fluid thickener solution, save time and cost, improve operating efficiency, and make it have better viscoelasticity, salt and temperature resistance, and degelling property, the present invention first synthesizes a new cationic monomer, and then copolymerizes non-ionic monomers, cationic monomers and anionic monomers to prepare a fast-dissolving terpolymer emulsion-type fracturing fluid thickener, so that it has excellent drag reduction performance at low concentrations and can be used as slippery water, and has excellent thickening performance at high concentrations and can be used as sand-carrying fluid.
[0004] The instant terpolymer emulsion type fracturing fluid thickener and preparation method of the present invention are characterized in that the fracturing fluid thickener is prepared from the following raw materials by inverse emulsion polymerization, and the raw materials include by mass percentage: Monomer: 10-20%; Emulsifier: 2.0-4.0%; Initiator: 0.02~0.05%; Liquid paraffin: 50~-60%; The balance was deionized water.
[0005] Preferably, the instant terpolymer emulsion fracturing fluid thickener is characterized in that the monomers are acrylamide, (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide and sodium p-styrene sulfonate, and the mass ratio of the three is 10-14:2-3:0.008-0.1.
[0006] Preferably, the instant terpolymer emulsion fracturing fluid thickener is characterized in that the emulsifiers are Span-80 and Tween-80, and the mass ratio of the two is 5:1.
[0007] Preferably, the instant terpolymer emulsion fracturing fluid thickener is characterized in that the initiator consists of ammonium persulfate and sodium sulfite, and the mass ratio of the two is 1:1.
[0008] Preferably, the instant terpolymer emulsion fracturing fluid thickener is characterized in that the oil-water mass ratio is 5.5-6.0:4.5-4.0.
[0009] Preferably, the instant terpolymer emulsion fracturing fluid thickener is characterized in that the monomer (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide has the structural formula: It is obtained by the reaction of N,N,N'-trimethyl-N'-propyleneethylenediamine (TMPEMA) and ethyl bromide; wherein TMPEMA is obtained by the reaction of allyl chloride and N,N,N'-trimethylethylenediamine in the presence of triethylamine alkaline catalyst, and the reaction formula is as follows:
[0010] Preferably, the monomer (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide used in preparing a fast-dissolving terpolymer emulsion-type fracturing fluid thickener is characterized in that the monomer synthesis method comprises the following steps:
[0011] S1. Add 0.11 mol of allyl chloride and 0.10 mol of N,N,N'-trimethylethylenediamine into a round-bottom flask containing 100 mL of acetone, stir the solution evenly with a magnetic stirrer, then add 5 g of alkaline catalyst triethylamine into the solution, heat to 30°C, continue to introduce N2 to react for 40 min, and rotary evaporate at 45°C for 30 min to obtain the intermediate product N,N,N'-trimethyl-N'-propyleneethylenediamine (TMPEMA);
[0012] S2. Dissolve 0.10 mol TMPEMA in 75 mL anhydrous acetonitrile, add 0.22 mol ethyl bromide, transfer to a high-pressure reactor, react at 60°C for 16 h, remove volatiles by reduced pressure distillation, wash with ether and dry in a vacuum oven to obtain the monomer (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide.
[0013] Preferably, the instant terpolymer emulsion type fracturing fluid thickener is characterized in that the synthesis method of the instant terpolymer emulsion type fracturing fluid thickener comprises the following steps:
[0014] S1. Stir and mix the emulsifier and liquid paraffin to obtain an oil phase;
[0015] S2. Add monomers of acrylamide, sodium p-styrene sulfonate, and (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide to deionized water, stir to completely dissolve, and adjust the pH of the aqueous phase to 8 with a 2% sodium hydroxide solution to obtain an aqueous phase;
[0016] S3. The oil phase was added to a three-necked flask, and the aqueous phase was slowly added dropwise to the oil phase at 500 rpm. After the addition, stirring and emulsifying was continued for 50 min to obtain a stable water-in-oil pre-emulsion;
[0017] S4. Connect the three-necked flask to nitrogen, a thermometer, and an initiator dropping tube, pass nitrogen for 15 minutes to remove oxygen, raise the temperature to 25-35°C, slowly drop the initiator, and react for 3-6 hours to obtain a fast-dissolving terpolymer emulsion-type fracturing fluid thickener.
[0018] The instant terpolymer emulsion type fracturing fluid thickener of the present invention has the following advantages:
[0019] (1) It has good thermal stability at 120℃; (2) It has good salt resistance, temperature resistance and shear resistance; (3) It meets the requirements of SY / T 6376-2008 General Technical Conditions for Fracturing Fluids; (4) At low concentrations, its drag reduction performance meets NB / T14003.1-2015 Shale Gas Fracturing Fluid Part 1: Performance Indicators and Evaluation Methods for Slippery Water, and it can be used as slippery water; (5) At high concentrations, its thickening performance meets SY / T 6376-2008 General Technical Conditions for Fracturing Fluids, and it can be used as sand-carrying fluid; (6) It can meet the needs of fracturing operations under different geological conditions; (7) It has excellent viscosity increasing and quick dissolving ability, good viscoelasticity, salt resistance, temperature resistance and gel breaking properties, and has good application prospects in offshore oil and gas fracturing and shale oil and gas fracturing; (8) The emulsion type fracturing thickener has a fast dissolution time, which is 30-60 minutes less than the solid powder dissolution time, saving construction time and improving operation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the rheological curve of the fracturing fluid thickener solution of Example 3 of the present invention at 120°C;
[0021] Figure 2 is the effect of the NaCl concentration of the present invention on the fracturing fluid thickener solution of Example 3;
[0022] Figure 3 is the effect of the CaCl2 concentration of the present invention on the fracturing fluid thickener solution of Example 3;
[0023] Figure 4 is the drag reduction rate curve of the slick water fracturing fluid system of Example 3 of the present invention;
[0024] Figure 5 This is the static filtration loss curve at 120°C of the fracturing fluid system of Example 3 described in the present invention. DETAILED DESCRIPTION
[0025] The present invention is not limited by the following embodiments, and specific implementation methods can be determined based on the technical solutions of the present invention and actual conditions. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art.
[0026] Example 1
[0027] The synthetic experimental steps of a fast-dissolving terpolymer emulsion type fracturing fluid thickener are as follows:
[0028] S1. 2.5 g of Span-80 emulsifier, 0.5 g of Tween-80 emulsifier and 52.0 g of liquid paraffin were stirred and mixed to obtain an oil phase;
[0029] S2. 12.0 g of acrylamide, 3.0 g of (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide, and 0.012 g of sodium p-styrene sulfonate were added to 29.988 g of deionized water, stirred to completely dissolve, and the pH of the aqueous phase was adjusted to 8 with 2% sodium hydroxide solution to obtain an aqueous phase;
[0030] S3. The oil phase was added to a three-necked flask, and the aqueous phase was slowly added dropwise to the oil phase at 500 rpm. After the addition, stirring and emulsifying was continued for 50 min to obtain a stable water-in-oil pre-emulsion;
[0031] S4. Connect the three-necked flask to nitrogen, a thermometer, and an initiator dropping tube, pass nitrogen for 15 minutes to remove oxygen, raise the temperature to 30°C, slowly drop 0.015g of ammonium persulfate and 0.015g of sodium sulfite, and react for 4 hours to obtain a fast-dissolving terpolymer emulsion-type fracturing fluid thickener.
[0032] Example 2
[0033] The synthetic experimental steps of a fast-dissolving terpolymer emulsion type fracturing fluid thickener are as follows:
[0034] S1. 2.0 g of Span-80 emulsifier, 0.4 g of Tween-80 emulsifier and 52.6 g of liquid paraffin were stirred and mixed to obtain an oil phase;
[0035] S2. 14.0 g of acrylamide, 2.0 g of (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide, and 0.08 g of sodium p-styrene sulfonate were added to 28.92 g of deionized water, stirred to completely dissolve, and the pH of the aqueous phase was adjusted to 8 with 2% sodium hydroxide solution to obtain an aqueous phase;
[0036] S3. The oil phase was added to a three-necked flask, and the aqueous phase was slowly added dropwise to the oil phase at 500 rpm. After the addition, stirring and emulsifying was continued for 50 min to obtain a stable water-in-oil pre-emulsion;
[0037] S4. Connect the three-necked flask to nitrogen, a thermometer, and an initiator dropping tube, pass nitrogen for 15 minutes to remove oxygen, raise the temperature to 30°C, slowly drop 0.020g of ammonium persulfate and 0.020g of sodium sulfite, and react for 5 hours to obtain a fast-dissolving ternary copolymer emulsion-type fracturing fluid thickener.
[0038] Example 3
[0039] The synthetic experimental steps of a fast-dissolving terpolymer emulsion type fracturing fluid thickener are as follows:
[0040] S1. 3.0 g Span-80 emulsifier, 0.6 g Tween-80 emulsifier and 55.4 g liquid paraffin were stirred and mixed to obtain an oil phase;
[0041] S2. 13.0 g of acrylamide, 3.0 g of (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide, and 0.1 g of sodium p-styrene sulfonate were added to 23.9 g of deionized water, stirred to completely dissolve, and the pH of the aqueous phase was adjusted to 8 with 2% sodium hydroxide solution to obtain an aqueous phase;
[0042] S3. The oil phase was added to a three-necked flask, and the aqueous phase was slowly added dropwise to the oil phase at 500 rpm. After the addition, stirring and emulsifying was continued for 50 min to obtain a stable water-in-oil pre-emulsion;
[0043] S4. Connect the three-necked flask to nitrogen, a thermometer, and an initiator dropping tube, pass nitrogen for 15 minutes to remove oxygen, raise the temperature to 30°C, slowly drop 0.018g of ammonium persulfate and 0.018g of sodium sulfite, and react for 6 hours to obtain a fast-dissolving terpolymer emulsion-type fracturing fluid thickener.
[0044] Thickener solubility and apparent viscosity testing
[0045] At a constant stirring rate of 300 rpm and a temperature of 25°C, a 0.2 wt% concentration of a fast-dissolving terpolymer emulsion-type fracturing fluid thickener, a polyacrylamide solid thickener, and a polyacrylamide emulsion-type thickener solution were prepared in beakers of the same size. The time when the viscosity no longer increases was determined as the dissolution time of the thickener, as shown in Table 1.
[0046] Table 1 Comparison of dissolution time of three thickeners (25°C, 0.2wt%)
[0047] As shown in Table 1, the three embodiments of the instant terpolymer emulsion type fracturing fluid thickener are completely dissolved within 5 minutes, while the dissolution time of the polyacrylamide solid thickener and the polyacrylamide emulsion type thickener is 56 minutes and 15 minutes respectively. It can be seen that the use of the thickener of the present invention can greatly save construction time and improve work efficiency. The apparent viscosity of the three embodiments of the instant terpolymer emulsion type fracturing fluid thickener after dissolution is greater than that of the polyacrylamide solid thickener and the polyacrylamide emulsion type thickener, and has a stronger thickening ability. The main reason is that the (N, N, N-trimethyl-N'-allyl-N', N'-dimethyl)-ethyl ammonium dibromide monomer unit on the polymer chain segment has two quaternary ammonium salt groups, and the polymer molecules become more extended, which increases the hydrodynamic volume of the polymer molecules in water, and the mean square end distance of the formed random coils is larger.
[0048] The apparent viscosity of 0.1wt%, 0.2wt%, and 0.3wt% instant terpolymer emulsion fracturing fluid thickener solutions was tested using a Brookfield viscometer at a temperature of 25°C, a No. 64 rotor, and a speed of 100 rpm. The test results are shown in Table 2.
[0049] Table 2 Apparent viscosity of instant terpolymer emulsion fracturing fluid thickener solution
[0050] It can be seen from Table 2 that as the concentration of the instant terpolymer emulsion fracturing fluid thickener solution increases, the apparent viscosity increases, among which Example 3 has the highest apparent viscosity at the same concentration, so other properties of the thickener are tested using Example 3.
[0051] Thickener temperature and shear resistance test
[0052] The heat and shear resistance of the product obtained in Example 3 was tested using a MARS rotational rheometer to prepare a 0.2 wt% terpolymer emulsion fracturing fluid thickener solution. Test conditions: initial temperature 30°C, heating rate 0.33°C / min, shear rate 170s -1 , heat up to 120℃, shear for 2h, the test results are as follows Figure 1 As shown. Figure 1 It can be seen that the viscosity of the solution after shearing is 127mPa·s. According to SY / T 6376-2008 "General Technical Conditions for Fracturing Fluids", the viscosity after shearing is required to be greater than 50mPa·s. The fast-dissolving terpolymer emulsion fracturing fluid thickener meets the construction requirements of high-temperature reservoirs.
[0053] Thickener salt resistance test
[0054] The apparent viscosity of the product obtained in Test Example 3 was tested at different CaCl2 concentrations and different NaCl concentrations for a 0.2 wt% instant terpolymer emulsion type fracturing fluid thickener solution. The experimental conditions were a twelve-speed rotary viscometer at room temperature for 170 s. -1 The test results are as follows Figure 2 and Figure 3 As shown. With the increase of salt concentration, the apparent viscosity of the instant terpolymer emulsion fracturing fluid thickener decreases. When the NaCl concentration is 15wt%, the apparent viscosity of the emulsion solution reaches 14.1mPa·s; when the CaCl2 concentration is 4wt%, the apparent viscosity of the solution reaches 23.4mPa·s, which has excellent salt resistance.
[0055] Fracturing fluid drag reduction performance test
[0056] The product obtained in Example 3 was used to prepare a slick water fracturing fluid system, using 0.01wt% of a fast-dissolving terpolymer emulsion-type fracturing fluid thickener, 0.15wt% of a drainage aid, 0.3wt% of an anti-swelling agent, and the remainder of clean water to form a slick water fracturing fluid formulation system. The drainage aid was a nonionic gemini fluorocarbon surfactant (FCF-206, brand Kramar) and methanol (the mass ratio of the two was 1:2); the anti-swelling agent was potassium chloride.
[0057] The test conditions for the drag reduction performance of the slickwater fracturing fluid system are: temperature 25°C, pipeline diameter 0.01m, pipeline length 3.95m, flow rate 42L / min; the test results are as follows Figure 4 The experimental results show that the drag reduction rate is 72.2%, the drag reduction effect is excellent, and it meets the national standards for the use of slippery water.
[0058] Fracturing fluid sand carrying capacity, gel breaking capacity, and static filtration test
[0059] The product obtained in Example 3 was used to prepare a high-concentration formula fracturing fluid system, the system composition including 0.2wt% terpolymer emulsion fracturing fluid thickener, 0.4wt% iron ion stabilizer, 1.5wt% anti-swelling agent, 0.5wt% cross-linking agent, 1.5wt% drainage agent, and the balance of clean water. The anti-swelling agent is KCl; the cross-linking agent is sodium borate; the drainage agent is a non-ionic gemini fluorocarbon surfactant (FCF-206, brand Kramar) and methanol (the mass ratio of the two is 1:2).
[0060] (1) The sand-carrying capacity of the high-concentration formula fracturing fluid system was tested. The fracturing fluid system was evenly mixed with quartz sand (20-40 mesh) with a content of 20wt%, 30wt%, and 40wt%, and placed in a measuring cylinder of a specific specification (100mL). According to the technical requirements of SY / T7627-2021 water-based fracturing fluid, at an oven temperature of 120°C, the sedimentation distance of the quartz sand was read as time went by. Four measurements were performed at 15min, 30min, 60min, and 120min, and the sedimentation rate was calculated (sedimentation rate = sedimentation distance / time); the test results are shown in Table 3.
[0061] Table 3 Sand-carrying settling velocity of high-concentration emulsion fracturing fluid system (120°C) Settling time (min) 15 30 60 120 Sedimentation rate of 20wt% quartz sand (cm / min) 0.00000 0.00670 0.050 0.0038 Sedimentation rate of 30wt% quartz sand (cm / min) 0.00033 0.00067 0.0067 0.0042 Sedimentation rate of 40wt% quartz sand (cm / min) 0.00670 0.0083 0.0580 0.0041
[0062] The experimental results show that at 120°C, in the first 60 minutes, in the high-concentration fracturing fluid system with 20wt%, 30wt%, and 40wt%, the sedimentation rates of quartz sand particles are 0.05cm / min, 0.0067cm / min, and 0.058cm / min, respectively. It is clearly observed that the sedimentation rate of quartz sand particles with 30wt% content is the smallest, which is the optimal amount of sand added. Under the action of gravity, the quartz sand content of 20wt% is low, the distance between quartz sand particles is large, the falling space is too large, and the sedimentation is faster; the quartz sand content of 40wt% is high, the distance between quartz sand particles is smaller, the gravity has a great influence, and the sedimentation speed is fast. However, the overall sedimentation rate is small, indicating that it has good viscoelastic sand carrying capacity.
[0063] (2) The degumming property of the high-concentration emulsion fracturing fluid system was tested. After adding different amounts of degumming agent ammonium persulfate to 50 mL of the fracturing fluid system, degumming was carried out in an oven at 120°C according to the technical requirements of SY / T 7627-2021 water-based fracturing fluid. The time for the fracturing fluid to be completely degummed was recorded, the viscosity and residue amount of the degumming fluid were measured, and the surface tension and interfacial tension of the degumming fluid were tested using a JJ2000 surface tension meter and a TX-500 ultra-low spinning drop interfacial tension meter (the oil phase was kerosene when measuring the interfacial tension). The test results are shown in Table 4.
[0064] Table 4 Debonding performance of high concentration emulsion fracturing fluid system (120℃)
[0065] The experimental results show that when the temperature is 120℃, the gel-breaking time of the emulsion fracturing fluid system is short. In high-temperature formations, for environmental pollution considerations, the amount of gel-breaking agent can be selected as 0.04wt%. At this time, the amount of gel-breaking agent is small and the gel-breaking time is short. In medium and low temperature formations, the amount of gel-breaking agent can be selected as 0.07wt%, and the surface tension of the gel-breaking liquid is ≤28mN / m, and the interfacial tension is ≤2mN / m, which meets the standard. It can be seen from Table 3 that the surface tension and interfacial tension of the gel-breaking liquid are low. On the one hand, the drainage agent is a surfactant, which reduces the surface and interfacial tension. On the other hand, the quaternary ammonium salt cations and sulfonate ions contained in the thickener are both hydrophilic groups, which also play the role of surfactants and can effectively reduce the surface and interfacial tension of the gel-breaking liquid. The residue content of each group of gel-breaking liquid tested is ≤600mg / L, and the test results meet the requirements of the general technical conditions of fracturing fluid. The test data after gel-breaking also meet the standard "General Technical Conditions for Fracturing Fluids", indicating that the thickener has good gel-breaking performance.
[0066] (3) Test the static filtration of high-concentration emulsion fracturing fluid system. According to the technical requirements of SY / T 7627-2021 water-based fracturing fluid, the initial filtration loss Q of the static filtration of the fracturing fluid system is tested under high temperature (120°C) conditions. SP , filtration rate V c And static filtration coefficient C3. Test results are as follows Figure 5 and Table 5.
[0067] Table 5 Static filtration parameters of high concentration emulsion fracturing fluid system (120℃) <![CDATA[Q SP Filtration coefficient (m / min 1 / 2 )]]> <![CDATA[V c Filtration rate (m / min)]]> <![CDATA[Initial filtration loss of C3 (m 3 / m 2 )]]> <![CDATA[7.5×10 -6 ]]> <![CDATA[1.2×10 -7 ]]> <![CDATA[2.178×10 -4 ]]>
[0068] The experimental results show that the initial filtration loss Q SP , filtration rate V c and static filtration coefficient C3 meet the standard (Q SP ≤1×10 - 2 m 3 / m 2 , V c ≤1×10 -4 m / min, C3≤6×10 -3 m / min 1 / 2 ), with good filtration performance.
[0069] In summary, the instant terpolymer emulsion-type fracturing fluid thickener developed by the patent of the present invention has fast dissolution, high apparent viscosity, good temperature resistance, shear resistance and salt resistance, and the prepared fracturing fluid system has excellent performance in drag reduction, sand carrying capacity, gel breaking, static filtration and other aspects, meets the corresponding index requirements of oil and gas field fracturing, and has good application prospects in offshore oil and gas and shale oil and gas development.
Claims
1. A fast-dissolving terpolymer emulsion-type fracturing fluid thickener, characterized in that: The fracturing fluid thickener is prepared from the following raw materials by inverse emulsion polymerization, and the raw materials include by mass percentage: Monomer: 10-20%; Emulsifier: 2.0-4.0%; Initiator: 0.02~0.04%; Liquid paraffin: 50-60%; The balance was deionized water.
2. The instant terpolymer emulsion fracturing fluid thickener according to claim 1, characterized in that: The monomers are acrylamide, (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide and sodium p-styrene sulfonate, and the mass ratio of the three is 10-14:2-3:0.008-0.
1.
3. The instant terpolymer emulsion fracturing fluid thickener according to claim 1, characterized in that: The emulsifiers are Span-80 and Tween-80, and the mass ratio of the two is 5:
1.
4. The instant terpolymer emulsion fracturing fluid thickener according to claim 1, characterized in that: The initiator is composed of ammonium persulfate and sodium sulfite, and the mass ratio of the two is 1:
1.
5. The instant terpolymer emulsion fracturing fluid thickener according to claim 1, characterized in that: The oil-water mass ratio is 5.5-6.0:4.5-4.
0.
6. The instant terpolymer emulsion fracturing fluid thickener according to claim 2, characterized in that: The monomer (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide is obtained by the reaction of N,N,N'-trimethyl-N'-propyleneethylenediamine (TMPEMA) and ethyl bromide; wherein TMPEMA is obtained by the reaction of allyl chloride and N,N,N'-trimethylethylenediamine in the presence of triethylamine in the presence of an alkaline catalyst.
7. The monomer (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide used for preparing a fast-dissolving terpolymer emulsion-type fracturing fluid thickener as claimed in claim 6, characterized in that: The monomer synthesis method comprises the following steps: S1. Add 0.11 mol of allyl chloride and 0.10 mol of N,N,N'-trimethylethylenediamine into a round-bottom flask containing 100 mL of acetone, stir the solution evenly with a magnetic stirrer, then add 5 g of alkaline catalyst triethylamine into the solution, heat to 30°C, continue to introduce N2 and react for 40 min, and rotary evaporate at 45°C for 30 min to obtain the intermediate product TMPEMA; S2. Dissolve 0.10 mol TMPEMA in 75 mL anhydrous acetonitrile, add 0.22 mol ethyl bromide, transfer to a high-pressure reactor, react at 60°C for 16 h, remove volatiles by reduced pressure distillation, wash with ether and dry in a vacuum oven to obtain the monomer (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide.
8. A fast-dissolving terpolymer emulsion type fracturing fluid thickener as described in claims 1-7, characterized in that: The method for preparing the instant terpolymer emulsion type fracturing fluid thickener comprises the following steps: S1. Stir and mix the emulsifier and liquid paraffin to obtain an oil phase; S2. Add monomers of acrylamide, sodium p-styrene sulfonate, and (N,N,N-trimethyl-N'-allyl-N',N'-dimethyl)-ethylammonium dibromide to deionized water, stir to completely dissolve, and adjust the pH of the aqueous phase to 8 with a 2% sodium hydroxide solution to obtain an aqueous phase; S3. The oil phase was added to a three-necked flask, and the aqueous phase was slowly added dropwise to the oil phase at 500 rpm. After the addition, stirring and emulsifying was continued for 50 min to obtain a stable water-in-oil pre-emulsion; S4. Connect the three-necked flask to nitrogen, a thermometer, and an initiator dropping tube, pass nitrogen for 15 minutes to remove oxygen, raise the temperature to 25-35°C, slowly drop the initiator, and react for 3-6 hours to obtain a fast-dissolving terpolymer emulsion-type fracturing fluid thickener.
Citation Information
Patent Citations
Temperature-resistant salt-resistant quick-dissolving thickening agent used for seawater-based fracturing fluid and preparation method thereof
CN106190088A
Multi-effect emulsion type thickening agent and preparation method thereof
CN113621106A
High temperature stable cross-linked polymers
WO2015042028A1
Cited By
Integrated clean variable-viscosity fracturing fluid thickening agent as well as preparation method and application thereof
CN121343062A